2023
DOI: 10.1186/s13018-023-04121-9
|View full text |Cite
|
Sign up to set email alerts
|

Duhuo Jisheng decoction alleviates neuroinflammation and neuropathic pain by suppressing microglial M1 polarization: a network pharmacology research

Chengcan Gao,
Yulong Zhao,
Tao Yang
et al.

Abstract: Background Neuropathic pain (NP) is the most prevalent form of chronic pain resulting from nerve damage or injury. Despite the widespread use of Duhuo Jisheng decoction (DHJSD) in traditional Chinese medicine (TCM) to treat chronic pain, the mechanism underlying its analgesic action remains unclear. Methods Using network pharmacology, we obtained DHJSD and NP-related target information from public databases to construct protein–protein interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“… 26 Through network pharmacology, researchers have found that Duhuo Jisheng decoction, Yuanhu Zhitong Formula, and Gelsemium elegans can treat NP through multi-components, multi-targets, and multi-pathways. 27–29 This study used network pharmacology to explore the potential analgesic mechanisms of LCH and verified these mechanisms using molecular docking techniques and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Through network pharmacology, researchers have found that Duhuo Jisheng decoction, Yuanhu Zhitong Formula, and Gelsemium elegans can treat NP through multi-components, multi-targets, and multi-pathways. 27–29 This study used network pharmacology to explore the potential analgesic mechanisms of LCH and verified these mechanisms using molecular docking techniques and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%